Use of Fuzzy Logic Methods for Statement of Diseases on the Basis of Symptomatic Model - E.V. Kashkin, E.; A. Debunov, A.; I. Antonova, I. (International Journal of Engineering and Technology, 2018)
Finding the answer to the problem of recognizing (diagnosis) patient’s state as a whole and its main systems is based on analysis and interpretation of the available data on current state of the patient and his medical history. An important stage of this process is development of a method of forming images of the patient’s condition, and models of nosological forms of the disease, which will solve the main task of automating the procedure of recognizing the patient’s condition using a multi-dimensional virtual image.